A STUDY TO ASSESS THE EFFECTIVENESS OF VIDEO ASSISTED TEACHING ON KNOWLEDGE REGARDING KANGAROO MOTHER CARE AMONG STAFF NURSES WORKING IN SELECTED HOSPITALS, AT JAIPUR - Ajmera, Chirag; Arora, Jyoti; Taneja, Nikhil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Kangaroo Mother Care (KMC) is an effective, low-cost, and evidence-based approach designed primarily for the care of low birth weight (LBW) and preterm infants. This method includes early, continuous, and prolonged skin-to-skin contact between the mother and the baby, along with exclusive breastfeeding. Numerous studies have demonstrated that KMC leads to improved thermoregulation, enhanced weight gain, increased rates of breastfeeding, and a significant reduction in neonatal morbidity and mortality. These outcomes are particularly vital in resource-limited settings like India, where access to incubators and advanced neonatal care is often limited. Despite its well-documented benefits, the practice of KMC is not consistently implemented in many healthcare settings. One major barrier is the lack of awareness, knowledge, and confidence among healthcare providers—especially staff nurses who are directly involved in neonatal care. Addressing this knowledge gap is essential for improving the quality of care provided to LBW infants. This study was undertaken to evaluate the effectiveness of a structured video-assisted teaching (VAT) program in enhancing the knowledge of staff nurses regarding KMC. A pre-experimental one-group pre-test–post-test design was used, involving 60 staff nurses at MJF Hospital, Jaipur. Participants were selected using purposive sampling. A structured questionnaire comprising 27 multiple-choice questions was administered before and after the educational intervention. The results revealed a statistically significant improvement in knowledge following the video-assisted teaching. The mean pre-test score was 10.97 (40.63%), which increased to 23.3 (86.29%) in the post-test, with a calculated t-value of 6.77 (p < 0.05), indicating a highly significant difference. These findings strongly support the use of visual teaching strategies in nurse education. The study concludes that video-assisted teaching is a powerful tool for improving nurse knowledge and supports its integration into routine training to promote the widespread and effective practice of KMC, ultimately contributing to better neonatal health outcomes. Moreover, this method of training can be adapted and implemented across various healthcare settings—from tertiary care centers to primary health centers—making it highly suitable for a country like India with wide disparities in healthcare access. The ability of video-based learning to provide consistent, repeatable, and visually engaging education makes it an ideal tool for in-service training, especially in busy clinical environments where time and resources for traditional classroom sessions are limited. Empowering nurses with practical, evidence-based knowledge through such accessible formats will not only improve their clinical competence but also encourage the adoption of KMC as a routine neonatal care practice. Ultimately, this contributes to the national goal of reducing neonatal morbidity and mortality through simple, sustainable, and family-centered interventions.